Halotolerant Rhizobacterial Strains Mitigate the Adverse Effects of NaCl Stress in Soybean Seedlings. (20th October 2019) - Khan, Muhammad Aaqil; Asaf, Sajjad; Khan, Abdul Latif; Adhikari, Arjun; Jan, Rahmatullah; Ali, Sajid; Imran, Muhammad; Kim, Kyung-Min; Lee, In-Jung
Abstract : Background . Salinity is one of the major abiotic constraints that hinder health and quality of crops. Conversely, halotolerant plant growth-promoting rhizospheric (PGPR) bacteria are considered biologically safe for alleviating salinity stress. Results . We isolated halotolerant PGPR strains from the rhizospheric soil of Artemisia princeps, Chenopodium ficifolium, Echinochloa crus-galli, and Oenothera biennis plants; overall, 126 strains were isolated. The plant growth-promoting traits of these isolates were studied by inoculating them with the soil used to grow soybean plants under normal and salt stress (NaCl; 200 mM) conditions. The isolates identified as positive for growth-promoting activities were subjected to molecular identification. Out of 126 isolates, five strains— Arthrobacter woluwensis (AK1), Microbacterium oxydans (AK2), Arthrobacter aurescens (AK3), Bacillus megaterium (AK4), and Bacillus aryabhattai (AK5)—were identified to be highly tolerant to salt stress and demonstrated several plant growth-promoting traits like increased production of indole-3-acetic acid (IAA), gibberellin (GA), and siderophores and increased phosphate solubilization. These strains were inoculated in the soil of soybean plants grown under salt stress (NaCl; 200 mM) and various physiological and morphological parameters of plants were studied. The results showed that the microbial inoculation elevated the antioxidant (SOD and GSH) level and K + uptake and reduced the Na + ion concentration. Moreover, inoculation of these microbes significantly lowered the ABA level and increased plant growth attributes and chlorophyll content in soybean plants under 200 mM NaCl stress. The salt-tolerant gene GmST1 was highly expressed with the highest expression of 42.85% in AK1-treated plants, whereas the lowest expression observed was 13.46% in AK5-treated plants. Similarly, expression of the IAA regulating gene GmLAX3 was highly depleted in salt-stressed plants by 38.92%, which was upregulated from 11.26% to 43.13% upon inoculation with the microorganism. Conclusion . Our results showed that the salt stress-resistant microorganism used in these experiments could be a potential biofertilizer to mitigate the detrimental effects of salt stress in plants via regulation of phytohormones and gene expression.